The ex vivo on-ECMO amputated human limb model of atherosclerosis. (3rd October 2022) - Hartley, A; Owen, S; Caga-Anan, M; Afoke, J; Shalhoub, J; Hassen, K; Mason, J; Haskard, D O; Khamis, R
Abstract: Introduction: The preclinical study of atherosclerosis has been traditionally centred around the use of small animal models, translating to large animal models prior to first-in-man studies. We propose to disrupt this paradigm by designing an ex vivo pump perfused "live" limb model, to enable the molecular targeting of atherosclerosis. Purpose: To develop and test a novel experimental model of atherosclerosis, based on perfusion of an amputated human limb, to reduce time spent in translational pipelines and reliance on animal preclinical atherosclerotic research. Methods: The novel model consists of taking a freshly amputated limb and incorporating it into an ex-situ pump-perfused bypass system (akin to ECMO) circulating warmed, oxygenated blood. A custom-made operating table was designed to allow the flow of venous blood back into the circuit. The outflow of the table was connected to an oxygenator followed by a pulsatile pump in series. A parallel circuit warms the system to 37°C using a thermocirculator. The circuit was connected to an outflow cannula sutured into the proximal end of the amputated limb artery, permitting the passage of an introducer sheath and guiding catheter for intravascular imaging and x-ray angiography (Figure 1A). The pump was set to provide an output of 15ml per stroke (to represent approximately 20% of clinical stroke volume), with an average pump rate of 70 strokes per minute (estimating a heart rate of 70 beats per minute). Thus, total pump output, or "cardiac output" to the limb was ∼1, 050 ml/min. Regular monitoring was performed using arterial blood gas analysis, with correction of pH, oxygenation, haemoglobin, lactate and electrolytes. All participants provided written informed consent, and ethical permission was granted by the Imperial College Healthcare Tissue Bank (REC Wales 17/WA/0161; subcollection CAR_RK_17_070). Results: The model has been successfully performed (n=3), maintaining oxygen saturations >99% for the length of perfusion (up to 6 hours). X-ray angiography (Figure 1B), intravascular ultrasound (Eagle Eye, Volcano, Philips; Figure 1C) and optical coherence tomography (Dragonfly Optis, Abbott Cardiovascular; Figure 1D) was performed. In one limb, indocyanine green, a near-infrared fluorescent dye (excitation 788/ emission 813nm) that localises to atherosclerotic plaque, was injected into the system (2 mg/kg) and left to circulate for 90-minutes. The arterial tissue (Figure 1E – posterior tibial [left] and fibular [right]) was then dissected, and fluorescence reflectance imaging performed at 790 nm on the extracted tissue (Figure 1F). This confirmed indocyanine green uptake in areas of calcific atherosclerotic plaque on intravascular ultrasound and optical coherence tomography. Conclusions: This is the first demonstration of this novel ex vivo on ECMO "living" limb experimental model of atherosclerosis, which shows promise for future studies in translational interventional imaging and molecular targeting. Funding Acknowledgement: Type of funding sources: Public Institution(s). Main funding source(s): Wellcome Trust Clinical Research Fellowship